2014
DOI: 10.1007/s12154-014-0115-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, molecular docking and antibacterial evaluation of new 1,4-naphthoquinone derivatives contains carbazole-6,11-dione moiety

Abstract: A new series of new 1,4-naphthoquinone derivatives containing carbazole-6,11-dione moiety, which has not been reported yet, has been synthesized from 1,4-naphthoquinone and 4-aminophenylsulfone involving a Michael addition, benzoylation, and Pd-catalyzed coupling. This set of compounds has been evaluated for in vitro antibacterial studies against different Gram-positive and Gramnegative bacteria, and most of the synthesized compounds exhibited good antibacterial activity and the minimum inhibitory concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Recently, antimicrobial activities of 1,4‐naphthoquinone derivatives have attracted much attention ,. Pingaew et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, antimicrobial activities of 1,4‐naphthoquinone derivatives have attracted much attention ,. Pingaew et al .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, antimicrobial activities of 1,4-naphthoquinone derivatives have attracted much attention. [15,16] Pingaew et al [17] reported the synthesis of novel 1,4-naphthoquinone-based sulfonamides and antimicrobial and anticancer potentials (compound I). Cardoso et al [18] performed the synthesis and antibacterial evaluation of sulfonamide-based lapachone derivatives (compound II).…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Naturally occurring quinones are well-known as clinically useful drugs for treating cancer. 21 Although most of the quinone derivatives show a potential cytotoxic prole against a number of cancer cell lines, 22 they are still associated with other pharmacological activities, such as antibacterial, 23 antifungal, 24 antiviral, 25 anti-inammatory, 26 and antimalarial. 27 The literature about the rational design of antimicrobials describes several aminoquinone compounds 28,29 (1-6) and halo-1,4-naphtoquinone derivatives 30 (7-8) with promising inhibitory effects against pathogenic bacteria ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In this direction, six bacterial pathogens such as V. cholera, S. typhi, P. aeruginosa, R. rhodochrous, M. smegmatis, and M. luteus were identified. Based on the promising antibacterial and antimicrobial activities exhibited by anthraquinones and proline [27][28][29] derivatives, we considered antibacterial activity for some representative amides synthesised by us. Minimum inhibitory concentration (MIC) values of the synthesized compounds (−)-4a, (+)-4a′, (−)-4b and (+)-4b′ were examined by microdilution plate assay against six bacterial pathogenic strains consisting of three Gram-positive and three Gram-negative strains.…”
Section: Biological Activitymentioning
confidence: 99%